Redox Control in Olefin Polymerization Catalysis by Phosphine–Sulfonate Palladium and Nickel Complexes. Issue 18 (12th May 2017) - Yang, Bangpei; Pang, Wenmin; Chen, Min
Abstract : Two phosphine–sulfonate ligands, bearing both the ferrocene and the bi‐aryl units, were prepared and characterized. The corresponding palladium and nickel complexes are active in ethylene polymerization. In both the palladium and the nickel systems, the oxidation of the ferrocene unit leads to a decrease in catalytic activities and the polymer molecular masses. Interestingly, the neutral palladium catalyst is not active for norbornene polymerization, while the oxidized analogue shows good activity. As such, switchable polymerization could be achieved. Abstract : Palladium and nickel catalysts bearing the ferrocene unit were prepared. Reversible oxidation and reduction of the metal catalysts are demonstrated. In this catalyst system, switchable reactivities in ethylene and norbornene polymerization are realized.